Creep Buckling of a Wedge-Shaped Floating Ice Plate - Staroszczyk, R.; Hedzielski, B. (Engineering Transactions, 2004)
The paper is concerned with the problem of creep buckling of a floating ice plate pressing against a rigid, vertical-walled, engineering structure of a finite length. The plate is modelled as a truncated wedge of a semi-infinite length and constant thickness, resting on a liquid base and subjected to transverse bending due to the elastic reaction of the base and in-plane axial compression due to wind and water drag forces. The ice is treated as a viscous material, with the viscosity varying with the depth of the ice cover. The results of numerical calculations, carried out by the finite-element method, show the evolution of creep buckles in the plate, and also illustrate the behaviour of the ice cover at different levels of the in-plane axial loading, at different temperatures across the ice, and for different geometries of the wedge-shaped plate.